Spacialization by the Krigage method in pluvial variabilities, evapotranspiration and evaporation in the State of Pernambuco – Brazil (Research, Society and Development, 2021)
The objective is to specialize, using the kriging method, the elements of precipitation, evapotranspiration and evaporation, likely at the 75% probability level for 187 municipalities, generating their letters and information for government decision makers. Precipitation and average temperature data were used to generate evapotranspiration and monthly evaporation using the water balance method according to Thornthwaite, with an average of 40 years. inverse of the squared distance in each series. The charts were generated by interpolating the probable data obtained from precipitation, evapotranspiration and evaporation, using the Surfer 8.0 program. The method used for data interpolation was ordinary kriging. The analysis carried out in this study represents an approximation of the potential in terms of climate, water resources and the real water needs for the main activities of socioeconomic importance, visualized through the water balance. The 75% probability of rainfall was taken in the summer and autumn seasons in the coastal region, in the Mata and Agreste zones. In the spring and winter seasons, rainfall contributions were due to local effects, orography and local scale systems causing weak to moderate rainfall in a short period of time. In the absence of meteorological elements necessary to determine evapotranspiration, the Thornthwaite equation can be used with reasonable precision to estimate evapotranspiration in the studied area.